Barb Wilson letter to Thomas Kent regarding fall sightings, November 30, 1983 - Wilson, Barbara L.et al (1983)
Letter from Barb Wilson to Thomas Kent discussing the recent weather and including a list of birds sighted by Barb Wilson and others. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1983. Epson - sheet feed/flatbed